Exploring the Impact of the COVID-19 pandemic on depression in middle-aged and older Canadians with diabetes: Insights on incidence, recurrence, and risk factors from the Canadian longitudinal study on aging - ZhiDi Deng, B.Sc, PharmD; Grace Li, PhD; Maria E. Rowsell, MSW, RSW; Dorina Cadar; Esme Fuller-Thomson, PhD (Archives of Gerontology and Geriatrics Plus)
Purpose: Individuals with diabetes have an elevated risk of depression. The occurrence of the COVID-19 pandemic may have further impacted the mental health of patients living with diabetes. This study aims to examine: 1) factors associated with the development of depression during the COVID-19 pandemic among individuals with diabetes without a history of depression; and 2) factors associated with the persistence or recurrence of depression during the pandemic among those with diabetes, and a pre-pandemic history of depression. Methods: Secondary analysis of four waves of the Canadian Longitudinal Study on Aging surveys. Canadian residents between the ages of 45–85 were recruited in 2012–2015 and subsequently completed three follow-up surveys. A total of 2,730 individuals with diabetes were included in this study. Results: Among those without a prior history of depression, the incidence of new depression was 12.9 % (95 % CI 11.3–14.4 %) during the pandemic. Among those with a history of depression, approximately half (48.5 %; 95 % CI 45.4–51.7 %) were depressed during the pandemic. Factors associated with increased risk of incident and recurrent depression during the pandemic among older adults with diabetes include being female, greater educational attainment, higher income/savings, functional limitations, loneliness/social isolation, chronic pain, family conflict, and difficulties accessing health care. Conclusion: Among Canadians living with diabetes, both the incidence and recurrence of depression increased during the pandemic. Continued efforts to support the psychological well-being of older adults with diabetes are needed.